Emissions Analysis of Railway Transportation in Java Island Indonesia for Climate Change Mitigation – Study Case in 2023 - Nurjani, Emilya; Astuti, Bernadetta Indri Dwi; Firmansyah, Anugrah Jorgi; Fawzia, Annisa Ayu; Sekaranom, Andung Bayu; Suarma, Utia (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
Rail transportations are among the most environmentally friendly modes of transportation due to their low per capita emissions and carbon footprint. This study aims to analyze the total CO2 emissions and per capita emissions of long-distance and local rail transports operating on the island of Java in 2023. Emission calculations were conducted using the IPCC methodology and Sebos’s approach, incorporating factors such as locomotive types, which predominantly use B30 biodiesel and electricity as energy sources. The results are presented in the form of spatial maps for a comprehensive visualization. Key findings indicate that high emissions and per capita emissions are not exclusively associated with rail transports operating in urban areas. Areas with high long-distance train emissions (> 30,000 tons of CO2) are OP VI Yogyakarta and OP VIII Surabaya. High per capita emissions (> 0.005 tons of CO2/capita/year) are OP I Jakarta and OP VII Madiun. Instead, factors such as travel frequency, route length, locomotive type, fuel type, and passenger volume significantly influence emission outcomes. Commuter trains contribute higher emissions than long-distance trains and local non-commuter trains. The highest total emissions were recorded for the Jabodetabek Commuter Line, amounting to 14,545,676 tons of CO2. This line also exhibited the highest per capita emissions due to its high operational frequency and daily service schedule. These findings highlight the need for strategies to optimize rail transports operations and minimize environmental impacts, particularly in high-frequency commuter services.